2023
DOI: 10.1084/jem.20221518
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 infection and recovery in children: Distinct T cell responses in MIS-C compared to COVID-19

Abstract: SARS-CoV-2 infection for most children results in mild or minimal symptoms, though in rare cases severe disease can develop, including a multisystem inflammatory syndrome (MIS-C) with myocarditis. Here, we present longitudinal profiling of immune responses during acute disease and following recovery in children who developed MIS-C, relative to children who experienced more typical symptoms of COVID-19. T cells in acute MIS-C exhibited transient signatures of activation, inflammation, and tissue residency which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 81 publications
3
5
0
Order By: Relevance
“…Children with MIS-C exhibit a unique cytokine and chemokine profile in the plasma, with higher levels of the pro-inflammatory cytokines, consistent with previous reports of cytokines in MIS-C serum (Butters et al, 2023;Consiglio et al, 2020;Gurlevik et al, 2022;Hoste et al, 2022;Rybkina et al, 2023;Sacco et al, 2022). Interestingly, we found high amounts of IL-32 in MIS-C, suggesting that IL-32 may be a new biomarker of MIS-C.…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Children with MIS-C exhibit a unique cytokine and chemokine profile in the plasma, with higher levels of the pro-inflammatory cytokines, consistent with previous reports of cytokines in MIS-C serum (Butters et al, 2023;Consiglio et al, 2020;Gurlevik et al, 2022;Hoste et al, 2022;Rybkina et al, 2023;Sacco et al, 2022). Interestingly, we found high amounts of IL-32 in MIS-C, suggesting that IL-32 may be a new biomarker of MIS-C.…”
Section: Discussionsupporting
confidence: 91%
“…Here, we present antibody and innate immune profiling of children who developed MIS-C compared to other control children and adults with a spectrum of COVID-19 disease severity. We found that children with MIS-C displayed a substantial neutralizing antibody response and a highly inflammatory and distinct cytokine milieu, consistent with what has been shown previously (Rybkina et al, 2023). These observations led us to the hypothesis that even though there are neutralizing antibodies, there is lingering SARS-CoV-2 infection in children with MIS-C because of a dysfunctional antibodymediated cellular response.…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations